PERSEPSI DOSEN TERHADAP LAYANAN APLIKASI E-LKD UIN AR-RANIRY DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTENCE MODEL (TAM) - Andika Prajana; Yuni Astuti (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2019)
Information technology and telecommunications have an influence on educational activities from the elementary school level as well as the tertiary level. Higher Education is a formal institution that is expected to produce competent workforce that is ready to face the industrial revolution 4.0 along with technological advancements. Work skills, adaptability and a dynamic mindset become challenges for human resources, one of which is as a lecturer at tertiary institutions. In an effort to supervise the quality of lecturers at UIN Ar-Raniry Banda Aceh, Indonesia against the Tri Dharma of Higher Education they use an online application based on E-LKD (Electronic "Lecturer Performance Report"). This application is used as a tool in reporting semester activities of lecturers and also as an assessment of tertiary environmental assessors in deciding the eligibility of certification allowances and remuneration allowances for UIN Ar-Raniry lecturers. The purpose of this research is to empirically prove the influence between perceived usefulnes, technology support and perceived ease of use variables on attitude toward and behavior intention in using features and services in E-LKD applications. The research uses the case study method, by looking at the characteristics of the problems related to the background and current conditions of the subjects studied, as well as their interactions with the environment. This study uses questionnaire data on 100 UIN-Raniry lecturers. The results of this study indicate that the variable perceived ease, quality of technological support and usefulness perception partially have a significant effect on lecturers' attitudes and behavior.